Atributos físicos de latossolos cultivados com cana-de-açúcar sob sistemas de usos do solo - Navarro Vasquez, Miriam [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The quantification of impact or effects of soil uses on the physical attributes is fundamental in the evaluation of soil physical quality and in the search of greater development of cultivation. The objective of this study was to evaluate the alteration of physical attributes of Eutroferric Red Oxisol (LVef) and Acric Oxisol (LVw) resulting of different soil uses, and the influence of these uses in the quality and quality of sugarcane. In 2008, the experiment was carried out in two areas, in an LVef with very clay texture (clay = 680 g kg-1) and in an LVw with clay texture (clay = 440 g kg-1), Jaboticabal-SP. It was used a randomized block design with five repetitions and four treatments. The four treatments were characterized by different soil uses in the reform period of sugarcane cultivation: soybean/pearlmillet/soybean (SPmS), soybean/ sunnheamp /soybean (SShS), soybean/fallow/soybean (SFS) and soybean (S). The soil sample was realized 40 months after planting sugarcane(June 2013) in layers of 0,00-0,10m and 0,10-0,20m of profundity. It was determined organic material (MO), aggregate stability index (ASI), average weighted diameter (MWD), soil resistance to penetration (RP), soil density (DS), total porosity (PT),macroporosity and microporosity. The soybean (S) provided higher MWD in layers of 0,00-0,10 and 0,10-0,20m in Latosols. The SFS use and soybean (S) provided higher and lower density (DS), respectively. Finally, the soil uses utilized in the two Latosols altered some physical attributes of soil (MWD, DS, ASI), but did not alter the productivity and total retrievable sugar of sugarcane cultivation

A quantificação do impacto ou efeitos dos usos do solo nos atributos físicos é fundamental na avaliação qualidade física do solo e para buscar o maior desenvolvimento da cultura. O objetivo deste trabalho foi avaliar as alterações dos atributos físicos de um Latossolo Vermelho eutroférrico (LVef) e de um Latossolo Vermelho ácrico (LVw) resultante dos diferentes uso do solo, além da influência deles na quantidade e qualidade do cultivo de canade- açúcar, O experimento foi implantado em 2008 em duas áreas em Jaboticabal, SP, em um LVef, com textura muito argilosa (argila = 680 g kg-1) e em um LVw com textura argilosa (argila = 440 g kg-1). O delineamento experimental foi em blocos casualizados com cinco repetições e quatro tratamentos, caracterizados por diferentes usos do solo no período de reforma do canavial: soja/milheto/soja (SMS), soja/crotalária/soja (SCS); soja/pousio/soja (SPS) e soja (S). A amostragem do solo foi realizada, 40 meses após o plantio de cana-de-açúcar em junho 2013, nas camadas de 0,00- 0,10 e 0,10-0,20m de profundidade. Determinaram-se matéria orgânica (MO), índice de estabilidade de agregados (IEA), diâmetro médio ponderado (DMP), resistência do solo à penetração (RP), densidade do solo (DS), porosidade total (PT), macroporosidade e microporosidade. O cultivo de soja proporcionou maior DMP nas camadas de 0,00-0,10 m e 0,10-0,20 m nos Latossolos. O uso SPS e cultivo de soja proporcionaram maior e menor densidade, respectivamente. Os usos do solo utilizados nos dois Latossolos estudados alteraram alguns (DMP, DS, IEA) dos atributos físicos do solo, mas não afetaram na produtividade e açúcar total recuperável (ATR) da cana-de-açúcar. Palavras-chave: usos do solo, DMP, IEA, DS
Keywords: Solo - Uso; Solos - Densidade; Fisica do solo; Cana-de-açúcar; Latossolos; Soil physics